Rater Reliability of the Hardy Classification for Pituitary Adenomas in the Magnetic Resonance Imaging Era - Mooney, Michael A.; Hardesty, Douglas A.; Sheehy, John P.; Bird, C. Roger; Chapple, Kristina; White, William L.; Little, Andrew S. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives The Hardy classification is used to classify pituitary tumors for clinical and research purposes. The scale was developed using lateral skull radiographs and encephalograms, and its reliability has not been evaluated in the magnetic resonance imaging (MRI) era.Design Fifty preoperative MRI scans of biopsy-proven pituitary adenomas using the sellar invasion and suprasellar extension components of the Hardy scale were reviewed.Setting This study was a cohort study set at a single institution.Participants There were six independent raters.Main Outcome Measures The main outcome measures of this study were interrater reliability, intrarater reliability, and percent agreement.Results Overall interrater reliability of both Hardy subscales on MRI was strong. However, reliability of the intermediate scores was weak, and percent agreement among raters was poor (12–16%) using the full scales. Dichotomizing the scale into clinically useful groups maintained strong interrater reliability for the sellar invasion scale and increased the percent agreement for both scales.Conclusion This study raises important questions about the reliability of the original Hardy classification. Editing the measure to a clinically relevant dichotomous scale simplifies the rating process and may be useful for preoperative tumor characterization in the MRI era. Future research studies should use the dichotomized Hardy scale (sellar invasion Grades 0–III versus Grade IV, suprasellar extension Types 0–C versus Type D).
Keywords: pituitary adenoma; rater reliability; transsphenoidal